Analisis pengetahuan perpajakan dan kepatuhan wajib pajak UMKM Kafe di Kecamatan Sario - Kaunang, Joshua Bryan; Kalangi, Lintje; Pangerapan, Sonny (Riset Akuntansi dan Portofolio Investasi, 2024)
One of the taxpayers who make a major contribution in the field of taxation is Micro, Small and Medium Enterprises (UMKM). Cafe-based UMKM in Manado City have increased every year, especially in Sario District. However, in general, the growth of UMKM is not accompanied by the development of their compliance and knowledge regarding taxes. The objectives of this study are first to analyze the compliance of UMKM cafe income taxpayers in Sario District, and second to determine the knowledge of UMKM cafe taxpayers in Sario District regarding general provisions and procedures for paying taxes. The research method used is descriptive qualitative. The informants in this study were 5 UMKM cafe business owners in Sario District, Manado City. Data collection was carried out through interviews, observations and documentation. The results of this study show two points in general. First, the compliance of UMKM cafe taxpayers in Sario District is good, where business owners already understand and carry out the basics of income tax compliance, but still need to be improved. Second, the knowledge of UMKM cafe taxpayers in Sario District varies, but is still lacking where their knowledge is limited in terms of tax procedures. This is thought to be due to the lack of socialization from the government to UMKM taxpayers. The results of the analysis revealed that business owners still find it difficult to understand tax education information, and more intensive socialization is needed from the government.